2018
DOI: 10.2306/scienceasia1513-1874.2018.44.303
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorative effect of black soybean and purple sweet potato to improve sperm quality through suppressing reactive oxygen species (ROS) in type 2 diabetes mellitus rat (Rattus novergicus)

Abstract: Overproduction of reactive oxygen species (ROS) will promote oxidative damage and can induce reproductive disorder. A therapeutic strategy to reduce effects of reproductive disorder is by maintaining the balance between ROS and antioxidants. Black soybean (BSB) contains phenolic compounds and has a greater antioxidant capacity than yellow soybean. Purple sweet potato (PSP) also has antioxidant capacity, due to the presence of anthocyanin, but is low in protein. The combination of BSB and PSP is expected to lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…30 Our previous study suggests that BSB and PSP combination decline blood glucose level in T2DM rats. 31 In line with the result, the BSB and PSP combination improved cellular damage through the decrease of necrotic cells in the pancreas. Furthermore, the improves in pancreatic cells are followed by the improves of IRS-1 function.…”
Section: Discussionsupporting
confidence: 69%
“…30 Our previous study suggests that BSB and PSP combination decline blood glucose level in T2DM rats. 31 In line with the result, the BSB and PSP combination improved cellular damage through the decrease of necrotic cells in the pancreas. Furthermore, the improves in pancreatic cells are followed by the improves of IRS-1 function.…”
Section: Discussionsupporting
confidence: 69%
“…Flavonoids contained in BST can immediately chelate free radicals and act as scavenger by donating hydrogen atom then flavonoid radical will react with the second free radical and form a stable quinone (Gofur et al, 2018). Anthocyanins contained in PSP can reduce ROS activity by donating electrons to free radicals from the hydroxyl group (-OH), which are attached to the phenolic ring.…”
Section: Resultsmentioning
confidence: 99%
“…The DM indicated rats were further divided into seven groups with four rats for each group: DM, DM treated with glibenclamide (0.6 mg/kg BW), DM treated with BST, DM treated with PSP, and DM treated with a combination of BST and PSP in 1:3, 2:2, and 3:1 ratios (C1, C2, and C3, respectively). Treatments were given for 30 days [ 17 ]. The long period of treatment was chosen asspermatogonia and spermatocytes in the seminiferous tubules has effect over agent exposure during spermatogenesis stages on 28+3 days [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Purple sweet potato (PSP) ( Ipomoea batatas L.; PSP) contains high anthocyanin and antioxidant properties that can improve blood and various organ damages caused by oxidative stress [ 15 , 16 ]. Our previous study suggested that non-fermented black soybean improves sperm quality in DM rats when combined with PSP [ 17 ]; however, limited information is available regarding the impact of black soybean tempeh (BST) on the sperm quality of T2DM individuals when combined with PSP. The antioxidant contents in both BST and PSP are expected to be therapeutic agents that can be used in DM treatments.…”
Section: Introductionmentioning
confidence: 99%